Dynamic OSR dithered sigma–delta modulation in solid state light dimming. (7th October 2011) - Orcioni, Simone; d'Aparo, Rocco; Lobascio, Armando; Conti, Massimo
SUMMARY Pulse width modulation (PWM) is the most common way to control switching regulation and digital dimming. This paper presents a way to implement digital dimming by means of a dithered sigma–delta modulator with dynamic oversampling ratio. The system has been modeled in SystemC‐WMS and implemented in a board using a commercial microcontroller. Simulation results show conducted electromagnetic interference reduction compared to PWM and flickering reduction with respect to classic sigma‐delta modulation. Copyright © 2011 John Wiley & Sons, Ltd.